Improving impact resistance and residual compressive strength of carbon fibre composites using un-bonded non-woven short aramid fibre veil. (June 2019) - Yuan, Bingyan; Tan, Bo; Hu, Yunsen; Shaw, Jeremy; Hu, Xiaozhi
Abstract: Laminar carbon fibre composites with weak ply interfaces were toughened with ultra-thin (less than 20 μm) un-bonded non-woven Short Aramid Fibre (SAF) veils in the form of home-made pre-pregs. The effects of SAF veil on impact behaviour and compressive strength after impact of Carbon Fibre Reinforced Polymer laminates with multiple ultra-thin SAF interfacial layers were investigated. Optical observation and X-ray micro-computed tomography were employed for intact inspection of external and internal damage after high energy penetration impact. 50.8% decrease in back-face deflection and inhibited in-plane delamination growth were seen when compared with unmodified laminates. Compression after impact tests were performed after low energy impact to assess damage tolerance. SAF veils increased the residual compressive strength by 38.6% and changed the damage mode from delamination dominated fracture to shear failure.